Female third party lymphocytes are effective for immunotherapy of patients with unexplained primary recurrent spontaneous abortion: A retrospective analysis of outcomes. (2nd November 2015) - Liang, Xu; Qiu, Tian; Qiu, Lihua; Wang, Xipeng; Zhao, Aimin; Lin, Qide
Abstract: Objectives Allogeneic lymphocytes of paternal origin or supplied by a male third party have been used for the treatment of recurrent spontaneous abortion. Few studies, however, have examined the use of female third party lymphocytes. Our purpose was to determine whether female third party lymphocytes could be used for immunotherapy of women with recurrent spontaneous abortion. Methods In this retrospective non-randomised cohort-controlled study, the medical records of patients with three or more spontaneous abortions who received immunotherapy with lymphocytes from their partner, a male third party or a female third party, as well as those who received no immunotherapy, from 1996 to 2012 were reviewed. All patients were negative for mixed lymphocyte culture reaction (MLR)-blocking antibodies. Immunotherapy was performed in 302 patients in two courses, while 53 patients received no immunotherapy. Results The pregnancy rates in patients who received lymphocytes from their partners, a male third party or a female third party, and in those not immunised, were 85.6%, 87.3%, 89.7%, and 79.3%, respectively ( p = 0.523);the live birth rates were 87.3%, 75.8%, 84.6%, and 40.5%, respectively ( p < 0.001). Conclusions We conclude that female third party lymphocytes can be used for immunotherapy in patients with recurrent spontaneous abortion. Chinese Abstract 摘要 目的 父源同种异体淋巴细胞或第三方男性供给淋巴细胞用于复发性自然流产的治疗。少数研究调查了女性第三方淋巴细胞的应用。我们的目的是验证女性第三方淋巴细胞是否可以用于复发性自然流产的免疫治疗。 方法 在这项回顾性非随机队列对照研究中回顾了自1996年至2012年, 接受配偶淋巴细胞, 男性第三方淋巴细胞或接受女性第三方淋巴细胞免疫治疗, 或未接受免疫治疗的三次或更多次自然流产的患者病历资料。所有患者的混合淋巴细胞培养反应(MLR)-封闭抗体均为阴性。302名患者接受了两个疗程的免疫治疗, 而53名患者未接受免疫治疗。 结果 接受配偶淋巴细胞, 男性第三方淋巴细胞, 女性第三方淋巴细胞和未接受免疫治疗的患者妊娠率分别为85.6%，87.3%，89.7%，和79.3% (p = 0.523)。活产率分别为87.3%, 75.8%, 84.6%和40.5% (p < 0.001) 。 结论 我们推断, 女性第三方淋巴细胞可用于复发性自然流产患者的免疫治疗。 关键词 免疫疗法；淋巴细胞；反复自然流产